2010
DOI: 10.1080/01639366.2010.521020
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Nutrition and Hydration at the End of Life

Abstract: Considerable controversy surrounds the issue of care at the end of life (EOL) for older adults. Technological advances and the legal, ethical, clinical, religious, cultural, personal, and fiscal considerations in the provision of artificial hydration and nutrition support to older adults near death are presented in this comprehensive review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 170 publications
(147 reference statements)
0
16
0
2
Order By: Relevance
“…No significant literature backs up the idea of providing artificial nutrition and hydration to extend life, and it may in fact decrease quality of life in elderly patients close to death. 11 In our study, the majority support providing only oral intake as tolerated in the context of CMO patient.…”
Section: Discussionmentioning
confidence: 89%
“…No significant literature backs up the idea of providing artificial nutrition and hydration to extend life, and it may in fact decrease quality of life in elderly patients close to death. 11 In our study, the majority support providing only oral intake as tolerated in the context of CMO patient.…”
Section: Discussionmentioning
confidence: 89%
“…This has to be respected by the treating team as long as collective autonomy does not harm the patient's voluntary will. If information about the specific preferences cannot be obtained, a conservative approach is recommended [67,68].…”
Section: Commentarymentioning
confidence: 99%
“…Also, there is serious worry of possible needs to use physical restraints and sedative drugs to prevent patient from pulling out feeding tube due to dementia-related agitation and lack of cognition [50,64]. Studies have shown that nearly two-thirds of nursing home residents get agitated and pull their feeding tubes within the first two weeks of insertion [65]. Also, there is disconcertment that PEG-fed demented individuals are going to be deprived the pleasure of eating as well as the natural human interactions that come with oral feeding [64].…”
Section: Other Burdens and Complicationsmentioning
confidence: 99%